17β-Estradiol induces proliferation of endometrial NK cells (CD56+) in postmenopausal women. (2nd November 2017) - Sho, T.; Hachisuga, T.; Koi, C.; Kurita, T.; Kagami, S.; Kawagoe, T.; Matsuura, Y.; Yoshimura, K.; Hisaoka, M.
Abstract: Objective: The aim of this report was to evaluate the impact of hormone replacement therapy (HRT) on lymphocytic infiltration of the endometrium in postmenopausal women. Method: This study included 58 Japanese patients who had undergone hysterectomy at the University Hospital of Occupational and Environmental Health, Japan. Before surgery, nine patients had received 17β-estradiol (E2), 0.72 mg transdermally for 2–8 weeks (E2 group); 16 patients had received an Estra-1, 3, 5(10)-triene-3, 16α, 17β-triol (E3) vaginal tablet 0.5 mg per month five times (E3 group); and 19 patients had received 17β-estradiol, 0.62 mg, and norethindrone acetate (P), 2.70 mg for 3–16 weeks (E2 + P group). Fourteen patients received no HRT (control group). We examined uterine tissue specimens immunohistochemically for CD45+, CD3+, CD4+, CD8+, CD20+, CD56+, and Ki67 antigen-positive cells. Results: The numbers of CD56 + cells were significantly increased in the E2 group compared with all other groups (E2 vs. E3: 7.0 vs. 0.75, p  = 0.017; E2 vs. E2 + P: 7.0 vs. 0.58, p  = 0.009; E2 vs. control: 7.0 vs. 0.43, p  = 0.010). The numbers of CD3+ cells were significantly increased in the E2 group compared with the control group (149.3 vs. 42.6, p  = 0.008). Conclusion: 17β-Estradiol induced the proliferation of endometrial uterine natural killer cells (CD56+) in postmenopausal women.